Influence of Teachers’ Professional Training and Development on Students’ Academic Performance in Public Secondary Schools in Ndhiwa Sub-County Homabay County, Kenya - Anyanga, Erick; Kwaba, Jacob (African Journal of Education and Practice, 2024)
Purpose: The persistent academic underperformance in public secondary schools in Kenyan rural areas has raised concerns among educators, policymakers, and local communities. The purpose of the study is to evaluate how teacher professional training and development influence academic performance. One of the key factors believed to have contributed to this challenge is the lack of sufficient and effective professional training and development programs for teachers. There is a growing need to examine how teachers' professional training and development influence students' academic outcomes. The problem this study seeks to address is the unclear and under-researched relationship between teachers' professional development and students' academic performance in Ndhiwa Sub-County. Methodology: The study used descriptive research design and 15 public secondary schools, 113 teachers and 522 students were involved in the study as study respondents. The study used document analysis and semi structured questionnaires to collect the quantitative data, which was analyzed through descriptive statistics (frequencies and percentages). Findings: The study reveals that teachers' professional training and development have a significant impact on students' academic performance in public secondary schools in Ndhiwa Sub-County. The findings also indicated that teachers who undergo continuous professional development are better equipped with modern teaching strategies, content knowledge, and student engagement techniques, which in turn positively influence students' academic outcomes. Teachers with higher levels of training and access to ongoing professional development demonstrate improved classroom management, increased use of learner-centered methodologies, and more effective assessment technique. Unique Contribution to Theory, Practice and Policy: From the study findings, the study recommends that schools and educational authorities should develop more structured and regular Continuous Professional Development (CPD) programs that focus on subject-specific training, pedagogical skills, and updated teaching methodologies. This is because the study findings likely indicate that teachers who engage in regular training and development show better performance in student outcomes. The education policy makers should come up with the programs that forge partnerships between secondary schools and local universities or teacher training colleges to provide advanced training opportunities and access to educational research.